Time of Grain Supplementation and Social Dominance Modify Feeding Behavior of Heifers in Rotational Grazing Systems - Bica, Gabriela Schenato; Pinheiro Machado Filho, Luiz Carlos; Teixeira, Dayane Lemos; de Sousa, Karolini Tenffen; Hötzel, Maria José (Frontiers in Veterinary Science, 2020)
Social hierarchy affects the access of animals to feed resources. On daily rotational pasture systems supplementation time may influence feeding behaviour. This trial was designed to test the effect of grain delivery time on feeding behaviour of heifers. Heifers divided into two groups according to breed (n=15 Braford and n=19 Jersey) were tested in a crossover design with two treatments: INITIAL - supplement at 8 am (entry time to a fresh paddock) and MIDDLE - supplement at 4 pm (middle time of paddock use). Animals entered a new paddock every morning, and grain supplement at 2kg/animal/day was offered at the fenceline (1m/animal). Then, ingestive and other behaviours were registered by direct visual observation through scan sampling at 2 min intervals for 1h after grain supply. Agonistic interactions were recorded continuously (instigator-victim) to build a social matrix whereby each heifer was defined as dominant, intermediate or subordinate. Weekly pasture samples were collected according to the order that animals left the feeding area, using the hand-plucking technique, to determine crude protein and fiber content. Heifers spent more time grazing on the INITIAL treatment (p<0.0001), but exhibited more behaviours on the MIDDLE treatment (p<0.0001). Dominant heifers spent more time eating grain (p=0.0008), whereas subordinate heifers spent more time grazing along the paddock (p=0.0067), but not along the fence (p=0.0008). Crude protein content of pasture samples was higher for the INITIAL treatment (p<0.0001). Behavioural interaction occurred with respect to the order of leaving the feeding area, social rank, and crude protein consumed (p= 0.04). Subordinate heifers consistently grazed more and ate less grain supplement than dominant and intermediate heifers. However, when grain supplement was offered at the time animals entered the paddock, more grazing activity took place during supplement feeding, and subordinate heifers could select a high-protein diet. In the INITIAL treatment, this means that subordinate animals could benefit from the better pasture available, keeping a distance from dominant heifers, reducing agonistic interactions and likely improving their welfare.